The Present and the Past of American Liberalism In Light of Slavery and Racial Injustice - E. G. Ponomareva (Vestnik MGIMO-Universiteta)
Book review: Gajić S. 2020. From Slave to Citizen: The Struggle of African Americans for the Recognition of Humanity. Belgrade, CATENA MUNDI. 294 p. (In Serbian) [Гаjић С. Од роба до грађанина. Борба афроамериканаца за признање човечности]